POTENSI KETERSEDIAAN AIR TANAH DI DESA LIMO KECAMATAN SALIMPAUNG KABUPATEN TANAH DATAR - SUMATERA BARAT - Garinas, Wahyu (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2008)
Ground water potential map showed that the Salimpaung in Tanah Datar District has very low water resources potential. Deep and shallow water resources were found in some places and in a limited area.Interpretation of imaging resistivity showed that water resources potential lies in P1 and P2 layers. This layers were found in 90 to 150 meters to the south of the mosque. The potential layer was found between 10 to 30 meter depth and thickness between 5 to 25 meter and lies in observation point between 50 – 125 meter. Water resources at layer P1, P2, P3 and P4 has medium to low potential and the water layers was interpreted as water trap above the rock layer. The other water resources potential were found at P5, P6 and P7, at 90 – 150 meter to the north of the mosque. The potensial aquifer lies beneath hard rock at depth 40 to 60 meter.